Longitudinal Trajectories of Study Characteristics and Mental Health Before and During the COVID-19 Lockdown - van Zyl, Llewellyn E.; Rothmann, Sebastiaan; Zondervan-Zwijnenburg, Maria A. J. (Frontiers in Psychology, 2021)
The ‘COVID-19 Lockdown’ has significantly disrupted the higher education environment within the Netherlands and led to changes in available study-related resources and study demands of students. These changes in study resources and study demands, the uncertainty and confusion about educational activities, the developing fear and anxiety about the disease, and the implementation of the COVID-19 lockdown measures, may have a significant impact on the mental health of students. As such, this study aimed to investigate the trajectory patterns, rate of change and longitudinal associations between study resources-demands and mental health of 141 university students from the Netherlands before and during the COVID-19 lockdown. The present study employed a longitudinal design and a piecewise latent growth modelling strategy to investigate the changes in study resources and mental health over a three-month period. The results showed that moderate levels of student resources significantly decreased before-, followed by a substantial rate of increase during lockdown. In contrast, study demands, and mental health was reported to be moderate and stable throughout the study. Finally, the growth trajectories of study resources-demands and mental health were only associated before the lockdown procedures were implemented. Despite growing concerns relating to the negative psychological impact of COVID-19 on students, our study shows that the mental health during the initial COVID-19 lockdown remained relatively unchanged.